The Obama phenomenon : toward a multiracial democracy - Henry, Charles P., 1947-; Allen, Robert L., 1942-2024; Chrisman, Robert (University of Illinois Press, 2011)
Perspectives on the Obama campaign and early administration.
Keywords: Obama, Barack -- Influence.; Obama, Barack; Democracy -- United States.; United States -- Race relations -- 21st century.; Presidents -- United States -- Election -- 2008.; United States -- Politics and government -- 2009-2017.; États-Unis -- Relations raciales -- 21e siècle.; États-Unis -- Politique et gouvernement -- 2009-2017.; HISTORY -- United States -- 21st century.; POLITICAL SCIENCE -- American Government -- National.; Democracy; Influence (Literary, artistic, etc.); Politics and government; Presidents -- Election; Race relations; United States; 2000-2099